Journal of the life, travels and Gospel labours of that faithful servant and minister of Christ, Job Scott. - Scott, Job, 1751-1793. (Tufts University. Tisch Library., 2016)
1 online resource (xii, [2], 360 p.); "A testimony from the Monthly Meeting of Providence concerning Job Scott."--P. iii-x.; Signatures: a⁶ chi1 B-2H⁶.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Indexed in: Evans32810; Indexed in: English short title catalogueW19882